Occult Leydig Cell Tumour Presenting as Bilateral Gynaecomastia. Case Report and Literature Review - A. B. Patel; L. Wilson; A. Rane (The Scientific World Journal)
Gynaecomastia is the most common benign breast disorder in men. Among the various causes, testicular malignancies are an uncommon, life-threatening condition requiring prompt diagnosis and treatment. The case of a 28-year-old man is discussed, who presented with a 6-month history of painful bilateral gynaecomastia with no abnormality on clinical or biochemical examination. The patient's symptoms spontaneously resolved within 4 weeks. He then represented 10 years later with similar symptoms and an associated secondary hypogonadism. Ultrasound imaging revealed a clinically occult, hypoechoic mass in the left testis (Leydig cell tumour on histology). Clinical and hormonal findings normalized following surgical excision. This report underlines the importance in clinical practice of ultrasonographic evaluation of the testis, in all patients with gynaecomastia, despite unremarkable findings on physical examination.